Economic issues and perspectives on innovation in new resistant grapevine varieties in France - Etienne Montaigne; Alfredo Manuel de Jesus Oliveira Coelho; Leila Khefifi (Wine Economics and Policy, 2016)
The arrival in France of new varieties resistant to downy mildew and powdery mildew calls into question the aims of this "revolution" in a sector dominated by tradition. The proposed evaluation reviews the historical experience of cross-breeding programmes from an evolutionist standpoint before analysing the responses to the new technological paradigm of resistance to disease. Taking account of the time periods, dating their implementation and describing the opportunities open to winemakers, the paper revisits the scientific controversies, the institutional blockages to be eliminated, the means of recognition and the prospects.
Keywords: 330; Environmental compliance; Grapevine varieties; Innovation